Profile and outcome of patients presenting with agrochemical poisoning to the emergency department - A Sivanandan; S R Abel; M Sanjay; Jolly Chandran; Karthik Gunasekaran; Kundavaram Paul Prabhakar Abhilash (Journal of Family Medicine and Primary Care, 2020)
Background: Deliberate self-harm (DSH) is one of the leading causes of mortality and morbidity in India. Agrochemicals are the most commonly used compounds for DSH. The spectrum of Agrochemicals in use varies from region to region and time period with newer compound being regularly introduced into the market. Methodology: This retrospective cohort study included patients presenting with agrochemical poisoning to the ED during January 2017 to December 2018. Patient data was retrieved form the ED triage registry software and clinical workstation, following which their hospital outcome was determined. Results: During the study period, 1802 patients presented with DSH among which Agrochemical poisoning comprised 33.5% (604/1802). The mean age was 31 years and incidence of agrochemical poisoning was found to be higher in young adults (16–30 years–55.8%). The prevalence was more common in males (62.4%). The common agrochemical compounds consumed were insecticides (91%), herbicides (4.3%), fungicides (1.5%), fertilizer (1.5%), and plant growth regulators (1.5%). Majority (80.96%) of the patients were discharged alive from the hospital, 17% left against medical advice due to bad prognosis and 12 patients (2%) died in the hospital. Conclusion: Insecticides (mainly Organophosphates) are the most common agrochemicals used for DSH. Their management is better understood leading to better outcomes compared to other chemicals. The proportion of agrochemical use in DSH has reduced over the last decade. Imidacloprid (Insecticide) and Plant growth regulators are the new compounds for which appropriate management is not yet established and more research is needed.